Actave.net – a web‐based tool for the analysis of seabird activity patterns from saltwater immersion geolocators. Issue 7 (23rd May 2015) - Mattern, Thomas; Masello, Juan F.; Ellenberg, Ursula; Quillfeldt, Petra
Summary: The recent development of miniaturized saltwater immersion geolocators has made it possible to track and record activity of even the smallest seabird species over extended periods of time. The resulting activity data comprise of various time stamps and immersion times integrated over 10‐min intervals. Generally, such data sets are large and complex which makes analysis a daunting task, especially in the absence of dedicated software solutions. We developed Actave.net as a freely accessible, web‐based (http://www.actave.net ) analysis tool for complex activity data that provides cloud‐based and automatic computation of daily aggregates of various activity parameters based on recorded immersion data. The tool furthermore calculates various astronomical parameters (e.g. moon illumination) based on locational information derived from geolocation. Actave.net provides maps and graphs for data exploration, download of processed data for modelling and statistical analysis, and tools for sharing results with other users (e.g. collaborators). Currently, the tool supports the most frequently used M‐Series immersion loggers (BAS/Biotrack Ltd), but support for a broader range of device types as well as expanded analysis functionality is planned for future releases.